DOUBLE TROUBLE: DCX MUTATION-ASSOCIATED SUBCORTICAL BAND HETEROTOPIA – A CASE REPORT - Babunovska, Marija; Boshkovski, Bojan; Isjanovski, Igor; Kuzmanovski, Igor; Kostovska, Irena; Plashevska Karanfilovska, Dijana; Cangovska Chepreganova, Tatjana; Cvetkovska, Emilija (Macedonian Neurological Society, 2025)
Background: Patients with epilepsy have an increased risk of fractures, partly due to antiepileptic therapy (AET) through reduced bone mineral density (BMD). Although bone loss is multifactorial, AET may play a significant role, but the exact mechanisms remain unclear. Aim: To investigate the association between AET use and decreased BMD in an unselected population of Macedonian patients with epilepsy. Internationally accepted guidelines for bone health monitoring in epilepsy are lacking, and in our country there are no standardized recommendations. Identifying highrisk groups is essential for the prevention of osteoporosis and fractures. Methods: A cross-sectional study was conducted on 95 patients older than 20 years, treated with AET for more than 2 years, who attended the Epilepsy Outpatient Department at the University Clinic of Neurology between January 1st, 2021 and January 31st, 2024. Data included DXA scan results and demographic information. Logistic regression and other statistical analyses were applied. Results: Osteopenia was present in 50.5% and osteoporosis in 20.0% of patients. Independent risk factors for reduced BMD were female sex, polytherapy with AET, comorbidities, menopause, older age, and longer epilepsy duration. Age >50 years and depression were significant in univariate analysis but not confirmed in multivariate analysis. Conclusion: Independent risk factors such as female sex, menopause, older age, lower BMI, polytherapy, epilepsy duration, and comorbidity were associated with decreased BMD in epilepsy patients. These findings emphasize the importance of using known risk factors as guidance to identify patients at high risk of osteoporosis and fractures.
Keywords: bone health; ASM; comorbidity of epilepsy